2012
DOI: 10.1007/s10267-011-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus flocculosipes sp. nov., a new potentially cultivatable species from the palaeotropics

Abstract: Agaricus flocculosipes is described as new from northern Thailand and Mayotte based on morphology and ITS sequence analysis. The new species is compared with similar taxa, and a comprehensive description, line drawings, and colored photographs are provided. Agaricus flocculosipes is distinguished among the species in section Arvenses by its relatively large sporocarps (110-180 mm in diameter), erect floccose squamules on the surface of the stipe, and relatively small basidiospores (less than 6.5 lm long). Phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…Several potentially new sections were revealed by phylogenetic analysis of ITS sequence data (Zhao et al 2011), but they comprised exclusively tropical and some subtropical species. There have been several recent studies on Agaricus with several new species reported from Australia, China and Thailand (Chen et al 2012Karunarathna et al 2014;Lebel 2013;Gui et al 2015;Lebel & Syme 2012;Li et al 2014;Thongklang et al 2014;Zhao et al 2012Zhao et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Several potentially new sections were revealed by phylogenetic analysis of ITS sequence data (Zhao et al 2011), but they comprised exclusively tropical and some subtropical species. There have been several recent studies on Agaricus with several new species reported from Australia, China and Thailand (Chen et al 2012Karunarathna et al 2014;Lebel 2013;Gui et al 2015;Lebel & Syme 2012;Li et al 2014;Thongklang et al 2014;Zhao et al 2012Zhao et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments on additional strains of each species are needed to assess polymorphism at these transferable loci. The percentage of SubSSR markers that were successfully amplified (Table ) is consistent with the degree of phylogenetic relatedness previously described for these species (Zhao et al ., , ). Thus, the more closely related the species was to A. subrufescens, the higher the percentage of SubSSR markers that gave successful amplification.…”
Section: Resultsmentioning
confidence: 99%
“…The third Agaricus voucher ICS031 ranges in an out-group position of all the other 39 Agaricus species of our analysis and could be related to the genus Hymenagaricus, close related to the Agaricus genus. All these strains were separated of others species of Agaricus like that strain (thoen7297) of Agaricus collected in Dakar market by Thoen in 2010 17 . Finally, the phylogenetic analysis of the three Agaricus related vouchers collected in Senegal are in favour of three new species, two (ICS 032 and ICS002) belonging to different section of the Agaricus genus and one (ICS031) belonging to a genus different but close related to the Agaricus one such as the Hymenoagaricus.…”
Section: Discussionmentioning
confidence: 96%